An efficient method for generation of bi-allelic null mutant mouse embryonic stem cells and its application for investigating epigenetic modifiers. Issue 21 (13th September 2017) - Fisher, Cynthia L.; Marks, Hendrik; Cho, Lily Ting-yin; Andrews, Robert; Wormald, Sam; Carroll, Thomas; Iyer, Vivek; Tate, Peri; Rosen, Barry; Stunnenberg, Hendrik G.; Fisher, Amanda G.; Skarnes, William C.
Abstract: Mouse embryonic stem (ES) cells are a popular model system to study biological processes, though uncovering recessive phenotypes requires inactivating both alleles. Building upon resources from the International Knockout Mouse Consortium (IKMC), we developed a targeting vector for second allele inactivation in conditional-ready IKMC 'knockout-first' ES cell lines. We applied our technology to several epigenetic regulators, recovering bi-allelic targeted clones with a high efficiency of 60% and used Flp recombinase to restore expression in two null cell lines to demonstrate how our system confirms causality through mutant phenotype reversion. We designed our strategy to select against re-targeting the 'knockout-first' allele and identify essential genes in ES cells, including the histone methyltransferase Setdb1 . For confirmation, we exploited the flexibility of our system, enabling tamoxifen inducible conditional gene ablation while controlling for genetic background and tamoxifen effects. Setdb1 ablated ES cells exhibit severe growth inhibition, which is not rescued by exogenous Nanog expression or culturing in naive pluripotency '2i' media, suggesting that the self-renewal defect is mediated through pluripotency network independent pathways. Our strategy to generate null mutant mouse ES cells is applicable to thousands of genes and repurposes existing IKMC Intermediate Vectors.